School Efforts in Instilling Religious Character Values Through School Culture at SMP Negeri 1 Teras Boyolali - Wahidah, Zakiyatul; Muhammad Wildan Shohib (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
In this challenging modern era, quality character development is essential to form a unique and meaningful personality. One effective way to achieve this is through a school culture-based approach. This method helps build character and provides a strong moral foundation for the learners. For this character development to run well, this approach needs to be applied consistently and planned so that it can have a sustainable positive impact. This study aims to describe the school's efforts to instill religious character values through school culture at SMP Negeri 1 Teras Boyolali. The type of research used in this study is qualitative research. The research approach used by the researcher is phenomenology, which uses data collection techniques with interviews, observations, and document studies. The results of this study conclude that the school's efforts in instilling religious character values through school culture at SMP Negeri 1 Teras Boyolali are by carrying out activities such as the implementation of 5S (Smile, Greeting, Greeting, Politeness, Courtesy), reading prayers together, reading asmaul husna, dhuha prayers and so on. Factors that support religious activities are student discipline, support from all school residents, monitoring from students, adequate facilities, and so on, in terms of implementation, one of the inhibiting factors is the lack of student awareness.